Adenosine 3',5'-phosphate phosphodiesterase and pheromone response in the yeast Saccharomyces cerevisiae. - Liao, H H (1981)
Theophylline, aminophylline, and isobutylmethylxanthine, compounds reported to be inhibitors of adenosine 3',5'-phosphate (cAMP) phosphodiesterase, prevented the alpha-factor-induced cell cycle arrest of Saccharomyces cerevisiae a cells. To determine whether the in vivo effect of these methylxanthines on yeast pheromone response was related to their known biochemical mode of action, two assays for cAMP phosphodiesterase based on affinity of the product of the reaction (5'-AMP) for boronate groups were developed and were used to monitor the activity of the low Km cAMP phosphodiesterase present in yeast extracts. It was found that the relative efficacy of the methylxanthines as inhibitors of this enzyme in vitro was correlated with the degree to which they antagonized alpha-factor action in vivo. These results were consistent with our previous proposal that pheromone action involves a lowering of cAMP level in the target cell.